Hotel managers’ perspectives of Airbnb operations in Accra Metropolis, Ghana - Rosemary Wunpini Issaka; Abednego Kofi Bansah; Conrad-Joseph Wuleka Kuuder (Research in Hospitality Management, 2022)
The study was conducted to ascertain hotel managers’ standpoints on the influx of Airbnb facilities in Ghana’s hospitality “arena” and the palpable effects. Employing a qualitative approach to data collection, the study made use of in-depth interview guides, engaging 33 hoteliers to elicit information. The disruptive innovative theory was adopted as a guide to the study. Data were analysed using Nvivo to “couch” themes to make meaning from the transcriptions. The results analysed revealed that a sizable proportion of hoteliers (27) were aware that Airbnb facilities operated in the study area, while a few others were hearing of them for the first time. It was revealed that services rendered by these facilities were “distinct”, making Airbnb more accepted by the youth. Other respondents opined that Airbnb constituted a “misgovernance” due to the unregulated nature of their services in the country. To others, it was an easy way for some property owners to evade taxation by listing on the website. Many hoteliers did not find their operations a challenge to their businesses due to their markedly different clientele, while to others these facilities posed a potential threat. The study recommends that the activities of Airbnb be regulated to make it easier for their inclusion in the tax net for revenue mobilisation for the state.